Structure reinforcing method and structure reinforcing structure
By using aqueous silicon hydroxide as a binding agent and adding silicate powder to the fiber-reinforced plastic sheets, combining high-flowability cement composite materials, the problem of intimate bonding between the fiber-reinforced plastic sheets and the cement surface is solved, and a high-strength bonding effect is achieved.
Patent Information
- Application Number
- JP2023181449
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, when using aqueous latex without combustion materials as a binding agent, it is difficult to effectively bond the fiber reinforced plastic sheet to the cement surface, resulting in the fiber reinforced plastic sheet to detach the cement surface before destruction.
Water-based silicon hydroxide is used as the binder, and silicate powder is added to the periphery of the fiber-reinforced plastic sheet to increase adhesion, while using a cement composite material with high flowability as the binder to ensure that it can penetrate fully between the fiber-reinforced plastic sheets.
The high-strength combination of fiber-reinforced plastic sheets and cement surfaces is achieved, which avoids the problem of fiber-reinforced plastic sheets leaving the cement surface before destruction, and improves the overall strength and durability of the structure.
Smart Images

Figure 2025070862000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for reinforcing a structure and a reinforcing structure for a structure. [Background technology]
[0002] In recent years, as methods for reinforcing existing or newly constructed structures, there have been known continuous fiber sheet bonding methods, such as a carbon fiber sheet bonding method or an aramid fiber sheet bonding method, in which a continuous fiber-reinforced sheet, such as a carbon fiber sheet or an aramid fiber sheet, is attached to or wrapped around the surface of the structure, as described in Patent Document 1, or a method in which a sheet in which a continuous fiber bundle is impregnated with an uncured matrix resin is bonded and then cured.
[0003] Additionally, in order to eliminate the need for on-site resin impregnation, an FRP plate adhesive reinforcement method has been developed in which factory-produced FRP plates with a thickness of 1 to 2 mm and a width of approximately 5 cm are adhered to the concrete surface using a putty-like adhesive resin.
[0004] Furthermore, Patent Document 2 discloses a method of reinforcing a structure, in which fiber reinforcement is impregnated with a matrix resin, multiple hardened continuous fiber-reinforced plastic strands are aligned in a curtain-like shape in the longitudinal direction, and the strands are fixed to each other with a strand fixing material to form a fiber-reinforced sheet (hereinafter sometimes simply referred to as a "fiber-reinforced sheet"), which is bonded to the surface of the structure with a bonding material to integrate it.
[0005] In these methods, a combustible material (specifically, for example, a dangerous material under the Fire Service Act) may be used as a binder for bonding a reinforcing material such as a fiber-reinforced sheet to a structure.
[0006] On the other hand, Patent Document 3 describes the use of a fire-retardant cement-based material as a binder. Patent Document 3 describes the problem that when a cement-based material is used as a binder, it is difficult to bond the fiber-reinforced sheet to the binder, and in some cases, the fiber-reinforced sheet peels off from the cement material before breaking, and indicates that sufficient performance is not achieved if the cement material is used as is.
[0007] In order to solve the above problems, Patent Document 3 describes the application of a joint adhesive in order to ensure performance even when a cement material is used as a binder.
[0008] In the examples, the adhesive used for this joint coating is a room temperature curing epoxy resin ("FJ-C Primer" (product name) manufactured by Nippon Steel Composites Co., Ltd. / currently FP-WEC manufactured by Nippon Steel Chemical & Material Co., Ltd.), which is flammable. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 3-224901 [Patent Document 2] JP 2008-63758 A [Patent Document 3] JP 2011-208352 A Summary of the Invention [Problem to be solved by the invention]
[0010] Patent Document 3 also discloses that an epoxy-based emulsion adhesive (water-based primer) can be used as a joint adhesive, but according to experiments by the present inventors, when using a non-combustible water-based primer as the joint adhesive to be applied to the fiber-reinforced sheet in the reinforcement method described in Patent Document 3, the adhesion performance between the hardened resin and the cement material is not fully exhibited, and although the breaking load is high, the fiber-reinforced plastic wires are pulled out, and it was found that sufficient adhesion required for structural reinforcement cannot be exhibited.
[0011] Therefore, even when a non-combustible cement material is used as a binder to reinforce a structure using fiber-reinforced sheets, in order to ensure sufficient reinforcing performance, a flammable resin-based adhesive is still required as a joint adhesive to be applied to the fiber-reinforced sheets.
[0012] An object of the present invention is to provide a method for reinforcing a structure in which a fiber-reinforced sheet is adhered to the surface of the structure with a binder made of polymer cement mortar, which can firmly adhere the fiber-reinforced sheet and the binder without using any hazardous materials under the Fire Service Act, and can prevent the fiber-reinforced sheet from peeling off from the binder before it breaks. [Means for solving the problem]
[0013] A first aspect of the reinforcing method is a method for reinforcing a structure in which a plurality of fiber-reinforced plastic strands containing reinforcing fibers are aligned in the longitudinal direction in a curtain-like shape, and the strands are fixed to each other with a strand fixing material, and the fiber-reinforced sheet is bonded to the surface of the structure with a binder, the method comprising the steps of: applying an aqueous epoxy primer having an aqueous epoxy resin main agent and a hardener to the surface of the structure; applying polymer cement mortar as the binder to the surface of the structure to which the aqueous epoxy primer has been applied; and pressing the fiber-reinforced sheet into the coating layer of the polymer cement mortar before the applied polymer cement mortar hardens, thereby embedding the fiber-reinforced sheet and bonding it to the surface of the structure, the fiber-reinforced sheet having inorganic powder attached to the outer periphery of the plurality of fiber-reinforced plastic strands, the polymer cement mortar having a flow value of 140 to 180 mm in a JIS flow test, and satisfying the flow test requirements of JHS-416-2004. The sagging amount in the section repair material quality standard test method is 10 mm or less, and the tensile strength in the uniaxial direct tensile strength test at 28 days is 2.5 N / mm 2 The cement composite material has a tensile stress of 35% or more of its tensile strength when the tensile strain reaches 1.5% in the test.
[0014] In the first embodiment of the reinforcing method, the fiber-reinforced sheet is made of a plurality of fiber-reinforced plastic strands with inorganic powder attached thereto, and the anti-slip effect of the inorganic powder enhances adhesion between the fiber-reinforced sheet and the polymer cement mortar. This makes it possible to firmly bond the fiber-reinforced sheet and the binder without using a dangerous material under the Fire Service Act (the joint adhesive in Patent Document 3), and to prevent the fiber-reinforced sheet from peeling off from the binder before it breaks.
[0015] Here, since the fiber-reinforced sheet is a sheet in which multiple fiber-reinforced plastic strands are aligned in a curtain-like shape in the longitudinal direction, when inorganic powder is attached to the outer periphery of the multiple fiber-reinforced plastic strands, the spaces between the multiple fiber-reinforced plastic strands become narrower.
[0016] In contrast, in the reinforcing method of the first aspect, the polymer cement mortar has a flow value of 140 mm or more in the JIS flow test, so that the polymer cement mortar has high fluidity, and when the fiber reinforced sheet is pressed against the applied layer of polymer cement mortar to embed it, the fiber reinforced plastic wires of the fiber reinforced sheet can easily pass through even narrow gaps between them. As a result, poor construction (poor adhesion between the fiber reinforced sheet and the binder) is suppressed, and the fiber reinforced sheet can be prevented from peeling off from the binder before it breaks.
[0017] Furthermore, the flow value of polymer cement mortar in the JIS flow test is 180 m or less, and the sagging amount in the JHS-416-2004 Sectional Repair Material Quality Standard Test Method is 10 mm or less, so that polymer cement mortar applied to the surface of a structure is prevented from falling off from the surface.
[0018] Furthermore, the polymer cement mortar had a tensile strength of 2.5 N / mm2 in a uniaxial direct tensile strength test at 28 days. 2 The tensile stress at a tensile strain of 1.5% in the test is 35% or more of the tensile strength.
[0019] For this reason, even if tensile stress is generated in the fiber-reinforced sheet due to deflection of a structure, etc., polymer cement mortar is less likely to crack (break), and the fiber-reinforced sheet is prevented from peeling off from the binder before it breaks.
[0020] In the reinforcing method of the second embodiment, the polymer cement mortar contains 0.9 to 1.5 vol % of reinforcing organic fibers in the first embodiment.
[0021] Here, if the reinforcing organic fiber contained in the polymer cement mortar is less than 0.9 vol.%, cracks (fracture) are likely to occur in the polymer cement mortar, which serves as a binder, when stress is generated in the fiber-reinforced sheet. If cracks (fracture) occur in the polymer cement mortar, it will not be able to perform its function as a binder, and the fiber-reinforced sheet may peel off from the binder before breaking.
[0022] On the other hand, if the reinforcing organic fiber contained in the polymer cement mortar exceeds 1.5 vol%, the viscosity of the polymer cement mortar increases extremely, making it difficult for the polymer cement mortar to pass between the fiber-reinforced plastic wires in the fiber-reinforced sheet, which may result in poor construction.
[0023] In contrast, in the reinforcing method of the second embodiment, the polymer cement mortar contains 0.9 to 1.5 vol% of reinforcing organic fiber, so that the polymer cement mortar is less likely to crack (fracture), and the viscosity of the polymer cement mortar is maintained low, allowing the polymer cement mortar to easily pass between the fiber-reinforced plastic wires of the fiber-reinforced sheet. As a result, poor application (poor adhesion between the fiber-reinforced sheet and the binder) is suppressed, and the fiber-reinforced sheet is prevented from peeling off from the binder before it breaks.
[0024] In the reinforcing method of the third embodiment, in the first or second embodiment, the reinforcing organic fibers contained in the polymer cement mortar have a fiber length of 6 to 12 mm and an aspect ratio of 120 to 1,200.
[0025] Here, if the fiber length of the reinforcing organic fibers contained in the polymer cement mortar is less than 6 mm, or if the aspect ratio of the reinforcing organic fibers is less than 120, cracks (fracture) are likely to occur in the polymer cement mortar, which serves as a binder, when stress is generated in the fiber-reinforced sheet. If cracks (fracture) occur in the polymer cement mortar, it will not be able to perform its function as a binder, and the fiber-reinforced sheet may peel off from the binder before breaking.
[0026] On the other hand, if the fiber length of the reinforcing organic fibers contained in the polymer cement mortar exceeds 12 mm, or if the aspect ratio of the reinforcing organic fibers exceeds 1200, the viscosity of the polymer cement mortar increases extremely, making it difficult for the polymer cement mortar to pass between the fiber-reinforced plastic wires of the fiber-reinforced sheet, which may result in poor construction.
[0027] In contrast, in the reinforcing method of the third aspect, as described above, the reinforcing organic fibers contained in the polymer cement mortar have a fiber length of 6 to 12 mm and an aspect ratio of 120 to 1200, so that the polymer cement mortar is less likely to crack (fracture), and the viscosity of the polymer cement mortar is maintained low, allowing the polymer cement mortar to easily pass between the fiber-reinforced plastic wires of the fiber-reinforced sheet. As a result, poor application (poor adhesion between the fiber-reinforced sheet and the binder) is suppressed, and the fiber-reinforced sheet is prevented from peeling off from the binder before it breaks.
[0028] In a fourth aspect of the reinforcement method, in any one of the first to third aspects, the polymer cement mortar contains fine aggregate, the maximum diameter of the fine aggregate being 0.2 to 1.2 mm, and the fine aggregate fraction (FM) value being 0.5 to 2.3.
[0029] Here, if the maximum diameter of the fine aggregate is less than 0.2 mm, or if the fine aggregate fraction (FM) is less than 0.5, the viscosity of the polymer cement mortar increases excessively, making mixing with a mixer difficult.
[0030] On the other hand, if the maximum diameter of the fine aggregate exceeds 1.2 mm, it may be difficult for the polymer cement mortar to pass between the fiber-reinforced plastic wires in the fiber-reinforced sheet, which may result in poor construction.
[0031] Furthermore, if the fiber fraction (FM) value exceeds 2.3, the viscosity of the polymer cement mortar increases extremely, making it difficult for the polymer cement mortar to pass between the fiber-reinforced plastic wires in the fiber-reinforced sheet, which may result in poor construction.
[0032] In contrast, in the reinforcement method of the fourth aspect, as described above, the polymer cement mortar contains fine aggregate, the maximum diameter of which is 0.2 to 1.2 mm, and the fractional fineness (FM) value is 0.5 to 2.3, so that the viscosity of the polymer cement mortar is kept low and the maximum diameter of the fine aggregate is kept small, allowing the polymer cement mortar to easily pass between the fiber-reinforced plastic wires of the fiber-reinforced sheet. As a result, poor construction (poor adhesion between the fiber-reinforced sheet and the binder) is suppressed, and the fiber-reinforced sheet is prevented from peeling off from the binder before it breaks.
[0033] A fifth aspect of the reinforcing method is any one of the first to fourth aspects, wherein the fiber-reinforced sheet has a spacing between the fiber-reinforced plastic strands that is more than 3 mm and not more than 10 mm.
[0034] Here, when the distance between the fiber-reinforced plastic strands is 3 mm or less, the gaps between the fiber-reinforced plastic strands are narrow, making it difficult for polymer cement mortar to pass between the fiber-reinforced plastic strands of the fiber-reinforced sheet.
[0035] On the other hand, if the distance between the fiber-reinforced plastic strands exceeds 10 mm, the number of fiber-reinforced plastic strands per unit area of the fiber-reinforced sheet decreases, and the reinforcing effect decreases.
[0036] In contrast, in the reinforcement method of the fifth aspect, as described above, the spacing between the fiber-reinforced plastic strands in the fiber-reinforced sheet is more than 3 mm and not more than 10 mm, so that polymer cement mortar can easily pass between the fiber-reinforced plastic strands in the fiber-reinforced sheet while suppressing a decrease in the reinforcing effect.
[0037] As a result, poor application (poor adhesion between the fiber-reinforced sheet and the binder) is suppressed, and the fiber-reinforced sheet is prevented from peeling off from the binder before it breaks.
[0038] In the reinforcing method of the sixth aspect, in any one of the first to fifth aspects, the inorganic powder adhering to the fiber-reinforced sheet has an average particle size of 0.900 mm or less and a density of 400 to 2000 g / m per unit area of the fiber-reinforced sheet. 2 It is attached.
[0039] Here, the adhesion amount per unit area of the fiber-reinforced sheet is 400 g / m 2 If the inorganic powder is less than this, the anti-slip effect of the inorganic powder is small, and the adhesion between the fiber-reinforced sheet and the polymer cement mortar is low, so that the fiber-reinforced sheet may peel off from the binder before it breaks or before the polymer cement mortar experiences cohesive failure.
[0040] On the other hand, when the inorganic powder attached to the fiber-reinforced sheet has an average particle size of more than 0.900 mm, or the amount of attachment per unit area of the fiber-reinforced sheet is more than 2000 g / m 2 If it exceeds this limit, the gaps between the fiber-reinforced plastic strands will become narrower, making it difficult for the polymer cement mortar to pass through the gaps between the fiber-reinforced plastic strands in the fiber-reinforced sheet, which may result in poor construction.
[0041] In contrast, in the reinforcing method of the sixth embodiment, as described above, the inorganic powder attached to the fiber-reinforced sheet has an average particle size of 0.900 mm or less and a density of 400 to 2000 g / m 2 per unit area of the fiber-reinforced sheet. 2 Because the inorganic powder is attached, the anti-slip effect of the inorganic powder maintains high adhesion between the fiber-reinforced sheet and the polymer cement mortar, making it easier for the polymer cement mortar to pass between the fiber-reinforced plastic wires of the fiber-reinforced sheet.
[0042] As a result, poor application (poor adhesion between the fiber-reinforced sheet and the binder) is suppressed, and the fiber-reinforced sheet is prevented from breaking or from peeling off from the binder before cohesive failure of the polymer cement mortar occurs.
[0043] In the seventh aspect of the reinforcement method, in any one of the first to sixth aspects, the spacing between the fiber-reinforced plastic strands is larger than the diameter of the inorganic powder, and the ratio of the diameter of the fiber-reinforced plastic strands in the fiber-reinforced sheet to the spacing between the fiber-reinforced plastic strands to the diameter of the inorganic powder is 1:0.5-5:0.03-1.
[0044] Here, when the ratio of the spacing between the fiber-reinforced plastic strands to the diameter of the fiber-reinforced plastic strands is less than 0.5, the spacing between the fiber-reinforced plastic strands is relatively narrow, making it difficult for polymer cement mortar to pass between the fiber-reinforced plastic strands of the fiber-reinforced sheet.
[0045] On the other hand, if the ratio of the spacing between the fiber-reinforced plastic strands to the diameter of the fiber-reinforced plastic strands exceeds 5, the area of the fiber-reinforced plastic strands per unit area of the fiber-reinforced sheet decreases, reducing the reinforcing effect.
[0046] In addition, when the ratio of the diameter of the inorganic powder to the diameter of the fiber-reinforced plastic strand is less than 0.03, the anti-slip effect of the inorganic powder is small, and the adhesion between the fiber-reinforced sheet and the polymer cement mortar is low, so that the fiber-reinforced sheet may peel off from the binder before it breaks.
[0047] On the other hand, when the ratio of the diameter of the inorganic powder to the diameter of the fiber-reinforced plastic strand exceeds 1, the gaps between the fiber-reinforced plastic strands become narrower, which makes it difficult for the polymer cement mortar to pass through the gaps between the fiber-reinforced plastic strands in the fiber-reinforced sheet, which may result in poor construction.
[0048] In contrast, in the reinforcement method of the seventh embodiment, as described above, the ratio of the diameter of the fiber reinforced plastic wires in the fiber reinforced sheet to the spacing between the fiber reinforced plastic wires to the diameter of the inorganic powder is 1:0.5-5:0.03-1, so that the anti-slip effect of the inorganic powder maintains high adhesion between the fiber reinforced sheet and polymer cement mortar, and the polymer cement mortar can easily pass between the fiber reinforced plastic wires in the fiber reinforced sheet.
[0049] As a result, poor application (poor adhesion between the fiber-reinforced sheet and the binder) is suppressed, and the fiber-reinforced sheet is prevented from peeling off from the binder before it breaks.
[0050] The eighth aspect of the reinforcement structure is a reinforcement structure for a structure in which a plurality of fiber-reinforced plastic strands containing reinforcing fibers are aligned in a curtain shape in the longitudinal direction, and the fiber-reinforced plastic strands are fixed to each other with a strand fixing material, and the fiber-reinforced sheet is bonded to the surface of the structure with a binder. The reinforcement structure includes: a primer layer formed on the surface of the structure by an aqueous epoxy primer having an aqueous epoxy resin main agent and a hardener; a binder layer formed on the surface of the primer layer by polymer cement mortar as the binder, and having a mixed layer in which the aqueous epoxy primer and the polymer cement mortar are mixed at the boundary with the primer layer; and a fiber-reinforced sheet embedded inside the binder layer, the fiber-reinforced sheet having inorganic powder attached to the outer periphery of the plurality of fiber-reinforced plastic strands, the polymer cement mortar having a flow value of 140 to 180 mm in a JIS flow test, and a flow value of 140 to 180 mm in a JIS flow test. The amount of sagging in the section repair material quality standard test method is 10 mm or less, the tensile strength in a uniaxial direct tensile strength test at a material age of 28 days is 2.5 N / mm2 or more, and the tensile stress when a tensile strain of 1.5% is reached in the same test is 35% or more of the tensile strength.
[0051] In the reinforced structure of the eighth embodiment, the fiber-reinforced sheet is made of a plurality of fiber-reinforced plastic strands with inorganic powder attached thereto, and the anti-slip effect of the inorganic powder enhances adhesion between the fiber-reinforced sheet and the polymer cement mortar. This makes it possible to firmly bond the fiber-reinforced sheet and the binder without using a dangerous material under the Fire Service Act (the joint adhesive in Patent Document 3), and to prevent the fiber-reinforced sheet from peeling off from the binder before it breaks.
[0052] Here, since the fiber-reinforced sheet is a sheet in which multiple fiber-reinforced plastic strands are aligned in a curtain-like shape in the longitudinal direction, when inorganic powder is attached to the outer periphery of the multiple fiber-reinforced plastic strands, the spaces between the multiple fiber-reinforced plastic strands become narrower.
[0053] In contrast, in the reinforced structure of the eighth embodiment, the polymer cement mortar has a flow value of 140 mm or more in the JIS flow test, so that the polymer cement mortar has high fluidity and can easily pass through narrow gaps between the fiber reinforced plastic wires of the fiber reinforced sheet when embedding the fiber reinforced sheet in the binder layer of polymer cement mortar. As a result, poor installation (poor adhesion between the fiber reinforced sheet and the binder) is suppressed, and the fiber reinforced sheet is prevented from peeling off from the binder before it breaks.
[0054] Furthermore, in the reinforced structure of the eighth embodiment, the binder layer has a mixture layer of the water-based epoxy primer and the polymer cement mortar at the boundary with the primer layer, which improves the adhesion between the primer layer and the binder layer.
[0055] Furthermore, the flow value of polymer cement mortar in the JIS flow test is 180 m or less, and the sagging amount in the JHS-416-2004 Sectional Repair Material Quality Standard Test Method is 10 mm or less, so that polymer cement mortar applied to the surface of a structure is prevented from falling off from the surface.
[0056] Furthermore, the polymer cement mortar had a tensile strength of 2.5 N / mm2 in a uniaxial direct tensile strength test at 28 days. 2 The tensile stress at a tensile strain of 1.5% in the test is 35% or more of the tensile strength.
[0057] For this reason, even if tensile stress is generated in the fiber-reinforced sheet due to deflection of a structure, etc., polymer cement mortar is less likely to crack (break), and the fiber-reinforced sheet is prevented from peeling off from the binder before it breaks. Effect of the Invention
[0058] According to the reinforcing method of the present invention, it is possible to firmly bond a fiber-reinforced sheet and a binder without using any hazardous materials under the Fire Service Act, and to prevent the fiber-reinforced sheet from peeling off from the binder before it breaks. [Brief description of the drawings]
[0059] [Figure 1] 1 is a schematic cross-sectional view showing a state in which a fiber-reinforced sheet is bonded to the surface of a structure with a binder by the reinforcing method according to the present embodiment. FIG. [Diagram 2] 4 is a schematic cross-sectional view for explaining a base treatment step in the reinforcing method according to the embodiment. FIG. [Diagram 3] FIG. 2 is a schematic cross-sectional view for explaining a primer application step in the reinforcement method according to the present embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view for explaining a mortar applying step in the reinforcing method according to the present embodiment. [Diagram 5] FIG. 2A shows a fiber-reinforced sheet according to the present embodiment, and FIG. 2B shows a fiber-reinforced plastic strand of the fiber-reinforced sheet according to the present embodiment. [Figure 6] FIG. 2 is a cross-sectional view showing a cross section of a fiber-reinforced sheet according to the present embodiment. [Figure 7] FIG. 1 is a schematic diagram of a test piece for a single-sided tensile shear test. [Figure 8] FIG. 2 is an explanatory diagram of a one-way tensile shear test. [Figure 9] Table 1 shows the evaluation results. [Figure 10] Table 2 shows the evaluation results. [Figure 11] FIG. 1 is a diagram showing an overview of a testing machine for a deck wheel load running test. [Figure 12] FIG. 13 is a diagram showing the state in which a fiber-reinforced sheet is placed on a test specimen in a deck wheel load running test. [Figure 13] FIG. 2 is a diagram showing a test specimen used in a deck wheel load running test. [Figure 14] 1 is a table showing the concrete mix of the test specimens used in the deck wheel load running test. [Figure 15] 1 is a graph showing loading conditions in a deck wheel load running test. [Figure 16] 13 is a graph showing test results in a deck wheel load running test. [Figure 17] 1 is a table showing the average particle size of various inorganic powders. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0060] Hereinafter, an example of an embodiment of the present invention will be described with reference to the drawings.
[0061] In this specification, a numerical range indicated using "to" means a range including the numerical values before and after "to" as the minimum and maximum values, respectively. In addition, in a numerical range described in a stepped manner in this specification, an upper limit or lower limit value described in a certain numerical range may be replaced with an upper limit or lower limit value of another stepped numerical range. In addition, in a numerical range described in this specification, an upper limit or lower limit value described in a certain numerical range may be replaced with a value shown in an example. In this specification, the amount of each component means the total amount of multiple substances when there are multiple substances corresponding to each component, unless otherwise specified.
[0062] <Reinforcement method> The reinforcement method according to this embodiment is a method for reinforcing a structure 90 in which a fiber-reinforced sheet 40 is bonded to a surface 90A of the structure 90 with a binder, as shown in Fig. 1. It has been found that this reinforcement method can reinforce the structure 90 without using hazardous materials (combustible materials) defined by the Fire Service Act by using a water-based epoxy primer 20, polymer cement mortar 50 as a binder, and the fiber-reinforced sheet 40.
[0063] In the following, first, a description will be given of the structure 90, the water-based epoxy primer 20, the polymer cement mortar 50, and the fiber-reinforced sheet 40. Then, each step of the reinforcement method, the effect of the reinforcement method, and an evaluation of the reinforcement method will be described.
[0064] <Structure 90> A structure 90 to be reinforced by the reinforcing method according to the present embodiment may be, for example, a concrete structure. An example of a concrete structure is a bridge deck. Examples of the concrete structure include a reinforced concrete structure having reinforcing bars inside, and an unreinforced concrete structure having no reinforcing bars inside.
[0065] In addition, concrete structures are not limited to bridge decks, but may include, for example, structures other than bridge decks (e.g., bridge girders and piers), tunnels, buildings, etc., as long as they are structures made of concrete.
[0066] Furthermore, the structure 90 is not limited to a concrete structure, but may be, for example, a structure made of mortar, ceramics, metal, glass, or the like, as long as it is a structure to be reinforced.
[0067] Hereinafter, the surface 90A of the structure 90 reinforced by the reinforcing method according to this embodiment may be referred to as the reinforced surface 90A. The reinforced surface 90A is, for example, the bottom surface of the structure 90 facing downward (specifically, the downward side in the direction of gravity). The reinforced surface 90A may be a side surface of the structure 90 (specifically, a surface along the direction of gravity or a surface inclined with respect to the direction of gravity), and in this embodiment, the reinforced surface 90A is, for example, a surface on which the polymer cement mortar 50 may drip (i.e., a surface excluding a horizontal surface facing upward in the direction of gravity).
[0068] <Water-based epoxy primer 20> The water-based epoxy primer 20 is an epoxy resin primer using water as a medium, and has the advantage of having a higher shear strength than the water-based acrylic primer, so the water-based epoxy primer is used in the present invention. There are water-based epoxy primers that use water-soluble epoxy resins and emulsion types, and further there are one-component curing types and two-component curing types, but the one preferably used in the present invention is the two-component water-based epoxy primer 20 of emulsion type having an epoxy resin main agent of emulsion type and a curing agent. The epoxy of the water-based epoxy primer 20 is exemplified by bisphenol type epoxy such as bisphenol A type epoxy and modified epoxy with acrylic resin, but is preferably acrylic modified epoxy. In addition, the curing agent is not particularly limited as long as it is a water-soluble amine-based curing agent.
[0069] The water-based epoxy primer 20 can be used in a ratio determined in advance according to the materials used (for example, the base agent and hardener are mixed in a weight ratio of 100:100). From the viewpoint of repairing concrete structures, a viscosity of 100 mPa s or less is preferable because it increases the permeability.
[0070] Specifically, as the water-based epoxy primer 20, for example, FP primer FP-EE manufactured by Nippon Steel Chemical & Material Co., Ltd. can be used.
[0071] <Polymer Cement Mortar 50> The polymer cement mortar 50 is a cement composite material that includes cement, fine aggregate, a cement-mixable polymer, and reinforcing organic fibers.
[0072] The cement can be selected in consideration of the on-site construction conditions, and is not particularly limited. For example, various Portland cements such as ordinary, early strength, moderate heat, and extra early strength, various mixed cements such as blast furnace cement in which fly ash or blast furnace slag is mixed with any of these Portland cements, rapid hardening cements, etc. can be used alone or in combination of two or more types.
[0073] In addition, known admixtures such as blast furnace slag powder, fly ash, silica fume, limestone powder, quartz powder, gypsum dihydrate, gypsum hemihydrate, anhydrous gypsum, quicklime-based expanding materials, and calcium sulfoaluminate-based expanding materials can be added to the cement.
[0074] As the fine aggregate, river sand, sea sand, mountain sand, crushed sand, No. 3 to No. 8 silica sand, limestone, slag fine aggregate, etc. can be used, and it is preferable to use fine aggregate such as silica sand and limestone whose grain size is adjusted and which does not contain fine powder or coarse aggregate. The mixing ratio can be 25 to 300 parts by mass, preferably 50 to 230 parts by mass, per 100 parts by mass of the above cement.
[0075] Examples of polymers for mixing with cement include liquid polymer emulsions and re-emulsified powder resins, and those specified in JIS A 6203 can be used. Specific examples include resins such as polyacrylic ester, styrene butadiene, ethylene vinyl acetate, vinyl acetate / vinyl versatate, and vinyl acetate / vinyl versatate / acrylic ester, and any of these can be appropriately selected and used alone or in combination as an emulsion.
[0076] Examples of reinforcing organic fibers include ultra-high molecular weight polyethylene fibers, vinylon fibers, nylon fibers, polyparaphenylene benzobisoxazole fibers (PBO fibers), para-aramid fibers, polyarylate fibers, and the like. These can be used alone or in combination of two or more.
[0077] In addition to the above materials, polymer cement mortar 50 may contain additives such as a setting retarder, a hardening accelerator, a thickener, an antifoaming agent, a foaming agent, an anti-rust agent, an antifreeze agent, a colorant, a water retention agent, a shrinkage reducing agent, and an expansion agent.
[0078] In this embodiment, polymer cement mortar 50 is a cement composite material having a flow value of 140 to 180 mm in the JIS flow test and a sagging amount of 10 mm or less in the JHS-416-2004 Section Repair Material Quality Standard Test Method.
[0079] The JIS flow test is a flow test conforming to JIS R 5201. If the flow value is less than 140 m, the fluidity of polymer cement mortar 50 decreases, and polymer cement mortar 50 becomes less likely to pass between fiber reinforced plastic strands 43 to which inorganic powder is attached in fiber reinforced sheet 40. If the flow value exceeds 180 m, polymer cement mortar 50 becomes more likely to drip from reinforced surface 90A.
[0080] In this embodiment, as described above, a cement composite material having a flow value of 140 to 180 mm in the JIS flow test is used from the viewpoint of preventing dripping of polymer cement mortar 50 from reinforced surface 90A while ensuring the fluidity of polymer cement mortar 50. Furthermore, from the above viewpoint, it is preferable to use a cement composite material having a flow value of 150 to 170 mm in the JIS flow test.
[0081] In addition, polymer cement mortar 50 had a tensile strength of 2.5 N / mm2 in a uniaxial direct tensile strength test at 28 days. 2The cement composite material has a tensile stress of 35% or more of its tensile strength when the tensile strain reaches 1.5% in the test.
[0082] The tensile strength in a uniaxial direct tensile strength test at 28 days was 2.5N / mm 2 If the tensile stress is less than this value, or if the tensile stress at the tensile strain of 1.5% in the test is less than 35% of the tensile strength, when tensile stress is generated in the fiber-reinforced sheet 40 due to deflection of the structure, etc., cracks (fracture) are likely to occur, and the fiber-reinforced sheet 40 may peel off from the bonding material before breaking.
[0083] In this embodiment, from the viewpoint of suppressing the occurrence of cracks (fractures) when tensile stress is applied to fiber-reinforced sheet 40, as described above, polymer cement mortar 50 is made of a polymer cement mortar having a tensile strength of 2.5 N / mm2 in a uniaxial direct tensile strength test at a material age of 28 days. 2 The cement composite material used must have a tensile stress of 35% or more when the tensile strain reaches 1.5% in the test. Furthermore, from the above viewpoint, the tensile strength must be 3.0 N / mm in the uniaxial direct tensile strength test at 28 days. 2 From the above viewpoint, it is preferable to use a cement composite material in which the tensile stress at the time when the tensile strain reaches 1.5% in the same test is 50% or more of the tensile strength.
[0084] The content of the reinforcing organic fibers in polymer cement mortar 50 is 0.9 to 1.5 vol %. If the content of the reinforcing organic fibers in polymer cement mortar 50 is less than 0.9 vol %, polymer cement mortar 50, which serves as a binder, is likely to crack (fracture) when stress is applied to fiber reinforced sheet 40. If cracks (fracture) occur in polymer cement mortar 50, it will not be able to perform its function as a binder, and fiber reinforced sheet 40 may peel off from the binder before breaking.
[0085] On the other hand, if the reinforcing organic fiber contained in polymer cement mortar 50 exceeds 1.5 vol.%, the viscosity of polymer cement mortar 50 increases extremely, making it difficult for polymer cement mortar 50 to pass between the fiber-reinforced plastic wires of fiber-reinforced sheet 40, and poor construction may occur.
[0086] In the present embodiment, as described above, the reinforcing organic fibers contained in polymer cement mortar 50 are set to 0.9 to 1.5 vol % from the viewpoint of ensuring the fluidity of polymer cement mortar 50 while suppressing cracking (fracture) of polymer cement mortar 50. From the above viewpoint, the reinforcing organic fibers contained in polymer cement mortar 50 are preferably 1.0 to 1.3 vol %.
[0087] The reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of 6 to 12 mm and an aspect ratio of 120 to 1200. When the reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of less than 6 mm or an aspect ratio of less than 120, polymer cement mortar 50, which serves as a binder, is likely to crack (fracture) when stress is applied to fiber reinforced sheet 40. When cracks (fracture) occur in polymer cement mortar 50, it is unable to perform its function as a binder, and fiber reinforced sheet 40 may peel off from the binder before breaking.
[0088] On the other hand, if the fiber length of the reinforcing organic fibers contained in polymer cement mortar 50 exceeds 12 mm, or if the aspect ratio of the reinforcing organic fibers exceeds 1200, the viscosity of polymer cement mortar 50 increases extremely, making it difficult for polymer cement mortar 50 to pass between the fiber-reinforced plastic wires of fiber-reinforced sheet 40, and poor construction may result.
[0089] In the present embodiment, from the viewpoint of ensuring the fluidity of polymer cement mortar 50 while suppressing cracking (fracture) of polymer cement mortar 50, as described above, the reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of 6 to 12 mm and an aspect ratio of 120 to 1200. From the above viewpoint, it is preferable that the reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of 8 to 10 mm. From the above viewpoint, it is preferable that the reinforcing organic fibers contained in polymer cement mortar 50 have an aspect ratio of 300 to 1000.
[0090] Polymer cement mortar 50 contains fine aggregate, the maximum diameter of which is 0.2 to 1.2 mm, and the granular fraction (FM) value is 0.5 to 2.3. If the maximum diameter of the fine aggregate is less than 0.2 mm, or if the granular fraction (FM) value is less than 0.5, the viscosity of polymer cement mortar 50 increases excessively, making it difficult to mix with a mixer.
[0091] On the other hand, if the maximum diameter of the fine aggregate exceeds 1.2 mm, it may be difficult for polymer cement mortar 50 to pass between the fiber-reinforced plastic wires of fiber-reinforced sheet 40, resulting in poor construction.
[0092] Furthermore, if the fiber fraction (FM) value exceeds 2.3, the viscosity of polymer cement mortar 50 increases extremely, making it difficult for polymer cement mortar 50 to pass between the fiber-reinforced plastic wires of fiber-reinforced sheet 40, which may result in poor construction.
[0093] In this embodiment, from the viewpoint of suppressing poor construction, as described above, the fine aggregate in polymer cement mortar 50 has a maximum diameter of 0.2 to 1.2 mm and a fine aggregate fraction (FM) value of 0.5 to 2.3. From the above viewpoint, it is preferable that the fine aggregate has a maximum diameter of 0.3 to 1.0 mm. From the above viewpoint, it is preferable that the fine aggregate fraction (FM) value is 0.8 to 2.0.
[0094] <Fiber reinforced sheet 40> 5(A), the fiber-reinforced sheet 40 is a sheet material that is adhered to a surface 90A to be reinforced of a structure 90 with polymer cement mortar 50 as a binder, thereby reinforcing the structure 90. This fiber-reinforced sheet 40 is formed by arranging a plurality of fiber-reinforced plastic wires 43 containing reinforcing fibers 42 in a curtain-like shape in the longitudinal direction and fixing the wires to each other with a wire fixing material. In this embodiment, the fiber-reinforced sheet 40 is disposed inside a binder layer 52 made of polymer cement mortar 50.
[0095] As the reinforcing fiber 42, for example, organic fibers such as aramid, PBO (polyparaphenylene benzbisoxazole), polyamide, polyarylate, polyester, etc., basalt fiber, fly ash fiber, carbon fiber, glass fiber, metal fiber such as steel fiber, etc., can be used alone or in combination of two or more kinds. However, examples of reinforcing fibers are not limited to these.
[0096] Specifically, as shown in Fig. 5(A)(B), a fiber sheet (so-called strand sheet) can be used as the fiber-reinforced sheet 40, in which a plurality of fiber-reinforced plastic strands 43 including reinforcing fibers 42 are aligned in a longitudinal direction in a curtain-like shape and the strands 43 are fixed to each other with a strand fixing material 45. As shown in Fig. 5(B), the fiber-reinforced plastic strands 43 are formed by impregnating the reinforcing fibers 42 with a matrix resin 47 and curing the matrix resin 47. For the matrix resin 47, a thermosetting resin such as a room-temperature curing or thermosetting epoxy resin, vinyl ester resin, acrylic resin, unsaturated polyester resin, or phenol resin, or a thermoplastic resin such as an in-situ polymerization type phenoxy resin, nylon, or vinylon can be used. Preferably, an epoxy resin, which is a thermosetting resin, is used.
[0097] In fiber reinforced sheet 40, the spacing between fiber reinforced plastic strands 43 (gap spacing S2 (see FIG. 6) not taking into account inorganic powder between fiber reinforced plastic strands 43) is more than 3 mm and not more than 10 mm. If the spacing between fiber reinforced plastic strands 43 is 3 mm or less, the spacing between fiber reinforced plastic strands 43 is narrow, making it difficult for polymer cement mortar 50 to pass between fiber reinforced plastic strands 43 of fiber reinforced sheet 40.
[0098] On the other hand, if the distance between the fiber-reinforced plastic strands 43 exceeds 10 mm, the number of fiber-reinforced plastic strands 43 per unit area of the fiber-reinforced sheet 40 decreases, and the reinforcing effect decreases.
[0099] In this embodiment, as described above, the distance between the fiber-reinforced plastic strands 43 is set to more than 3 mm and not more than 10 mm from the viewpoints of the ease of passage of polymer cement mortar 50 and the reinforcing effect of fiber-reinforced sheet 40. Furthermore, from the above viewpoints, the distance between the fiber-reinforced plastic strands 43 is preferably more than 3 mm and not more than 9 mm, and more preferably more than 4 mm and not more than 7 mm.
[0100] <Inorganic Powder Used in Fiber Reinforced Sheet 40> In the fiber reinforced sheet 40 , inorganic powder is attached to the outer periphery of a plurality of fiber reinforced plastic strands 43 .
[0101] The inorganic powder attached to the fiber-reinforced sheet 40 has an average particle size of 0.900 mm or less and a density of 400 to 2000 g / m 2 per unit area of the fiber-reinforced sheet 40. 2 If the inorganic powder adhering to the fiber-reinforced sheet 40 has an average particle size of more than 0.900 mm, the inorganic powder will get caught on the rubber spatula when the fiber-reinforced sheet 40 is pressed down to embed the inorganic powder, which reduces workability, and the amount of adhesion per unit area of the fiber-reinforced sheet 40 will exceed 400 g / m. 2If the average particle size is less than 0.07 mm, the anti-slip effect of the inorganic powder is small, and the adhesion between fiber-reinforced sheet 40 and polymer cement mortar 50 is low. As a result, fiber-reinforced sheet 40 may peel off from the binder before breaking. Although there is no particular restriction on the lower limit of the average particle size, if the average particle size is too small, the safety, workability, and material costs of the attachment work to the fiber-reinforced sheet are deteriorated, so that the average particle size is preferably set to 0.07 mm or more.
[0102] On the other hand, when the inorganic powder adhered to the fiber-reinforced sheet 40 has an average particle size of more than 0.900 mm, or the amount of adhesion per unit area of the fiber-reinforced sheet 40 is more than 2000 g / m 2 If it exceeds this value, the gaps between the fiber reinforced plastic strands 43 become narrower. As a result, it becomes difficult for the polymer cement mortar 50 to pass through the gaps between the fiber reinforced plastic strands 43 of the fiber reinforced sheet 40, which may result in poor application.
[0103] The fiber reinforced plastic strands 43 are larger in diameter than the inorganic powder, and the ratio of the diameter of the fiber reinforced plastic strands 43 in the fiber reinforced sheet 40, the spacing between the fiber reinforced plastic strands 43 (gap spacing S2 (see Figure 6) between the fiber reinforced plastic strands 43 without taking into account the inorganic powder), and the diameter of the inorganic powder is 1:0.5~5:0.03~1.
[0104] When the ratio of the spacing between fiber reinforced plastic wires 43 to the diameter of fiber reinforced plastic wire 43 is less than 0.5, the spaces between fiber reinforced plastic wires 43 are relatively narrow, and polymer cement mortar 50 has difficulty passing between fiber reinforced plastic wires 43 of fiber reinforced sheet 40.
[0105] On the other hand, if the ratio of the spacing between the fiber-reinforced plastic strands 43 to the diameter of the fiber-reinforced plastic strands 43 exceeds 5, the area of the fiber-reinforced plastic strands 43 per unit area of the fiber-reinforced sheet 40 decreases, and the reinforcing effect decreases.
[0106] Furthermore, when the ratio of the diameter of the inorganic powder to the diameter of the fiber-reinforced plastic strands 43 is less than 0.03, the anti-slip effect of the inorganic powder is small, and the adhesion between the fiber-reinforced sheet 40 and the polymer cement mortar 50 is low. For this reason, the fiber-reinforced sheet 40 may peel off from the binder before breaking.
[0107] On the other hand, when the ratio of the diameter of the inorganic powder to the diameter of the fiber reinforced plastic strands 43 exceeds 1, the spaces between the fiber reinforced plastic strands 43 become narrower. As a result, it becomes difficult for the polymer cement mortar 50 to pass between the fiber reinforced plastic strands 43 of the fiber reinforced sheet 40, which may result in poor construction.
[0108] The ratio of the diameter of the fiber reinforced plastic strands 43 of the fiber reinforced sheet 40, the distance between the fiber reinforced plastic strands 43, and the diameter of the inorganic powder is preferably 1:0.5-5:0.1-1.
[0109] The inorganic powder preferably has an average particle size (D50) of 0.90 mm or less in the particle size distribution measured according to JIS Z 2601, and from the viewpoint of preventing the strand sheet from being pulled out due to the destruction of the inorganic powder itself, has a Mohs hardness of 3 or more. Specifically, crushed silica sand selected from No. 4 silica sand (average particle size: 0.887 mm), No. 5 silica sand (average particle size: 0.511 mm), No. 6 silica sand (average particle size: 0.294 mm), No. 7 silica sand (average particle size: 0.129 mm), No. 8 silica sand (average particle size: 0.073 mm), or a mixture thereof, crushed limestone selected from Hakuryu crushed stone of 1 rin (average particle size: 0.4 mm), 2 rin (average particle size: 0.7 mm), 3 rin (average particle size: 1.0 mm), etc. The preferred aggregates are fine aggregates of natural materials such as blast furnace slag fine aggregate of similar grain size to those mentioned above, river sand, sea sand, mountain sand, crushed sand, etc., fine powder of ceramic materials such as graphite, silica, alumina, etc., or mixtures thereof. However, taking into consideration cost and workability, silica sand selected from No. 4, No. 5, No. 6, No. 7 silica sand, or 1 rin, 2 rin, or 3 rin Hakuryu crushed stone, and mixtures of these silica sands and Hakuryu crushed stone are more preferred (see Figure 17).
[0110] Regarding the form of attachment of the inorganic powder to the fiber-reinforced sheet 40, it is preferable that the inorganic powder is attached evenly to the surface of the fiber-reinforced plastic strands constituting the fiber-reinforced sheet 40. In addition, the amount of attachment of the inorganic powder (per unit area of the sheet (m 2 per unit) 400~2000g / m 2 ) is ensured, the inorganic powder may be attached to the entire surface of the fiber-reinforced sheet, or may be attached at regular intervals in the longitudinal direction of the sheet, or may be attached in a patchy pattern. The powder is attached by using an adhesive or binder, or by softening the matrix resin of the fiber-reinforced plastic strand by heating or the like to fuse or melt it.
[0111] <Other Examples of Fiber Reinforced Sheet 40> An example of the fiber reinforced sheet is not limited to the fiber reinforced sheet 40 shown in FIGS. 5(A) and 5(B).
[0112] The fiber reinforced sheet 40 may be, for example, a fiber reinforced sheet in which a plurality of belt-shaped FRP plates (one example of fiber reinforced plastic wires) containing reinforcing fibers 42 are arranged at equal intervals so as to be parallel to the longitudinal direction, and the FRP plates are fixed to each other with a wire fixing material. The width of the belt-shaped FRP plate is preferably 10 to 50 mm, and the plate thickness and the intervals between the FRP plates are similar to those of the fiber reinforced sheet using fiber reinforced plastic wires 43.
[0113] The fiber-reinforced sheet 40 is a fiber-reinforced sheet in which a plurality of fiber-reinforced plastic strands 43 including reinforcing fibers 42 are aligned in the longitudinal direction and fixed to each other with a strand fixing material, and the strands 43 may be bundled into a belt shape, arranged with an interval of 3 to 5 mm between each belt, and fixed with a wire fixing material. Note that the width of the belt portion in which the strands 43 are bundled is preferably about 5 to 50 mm, and other shapes and the like are similar to those of the fiber-reinforced plastic strands 43. The structure of the belt portion is not particularly limited, and it may be fastened using a wire fixing material, or may be fused using an adhesive.
[0114] <Each step of the reinforcement method> The reinforcing method according to the present embodiment specifically includes a base treatment step, a primer application step, a mortar application step, and an adhesion step. Each step of the reinforcing method will be described below.
[0115] <Surface preparation process> In the surface preparation step (see FIG. 2), a surface preparation step is performed to remove protrusions, attachments, deteriorated layers, and the like from the reinforced surface 90A of the structure 90. Removal of the protrusions, attachments, and deteriorated layers is performed using removal means such as a disk sander, sand blasting, steel shot blasting, and water jet. Note that the surface preparation step is not essential, and does not have to be performed.
[0116] <Primer application process> In the primer application step (see FIG. 3), a water-based epoxy primer 20 is applied to the surface to be reinforced 90A of the structure 90. If a base preparation step has been performed, the water-based epoxy primer 20 is applied to the surface to be reinforced 90A that has been subjected to base preparation.
[0117] Through the primer application step, a primer layer 22 made of the water-based epoxy primer 20 is formed on the surface 90A of the structure 90 to be reinforced.
[0118] <Mortar application process> The mortar application step (see FIG. 4) is a step of applying polymer cement mortar 50 to the reinforced surface 90A of the structure 90 to which the water-based epoxy primer 20 has been applied. In the mortar application step, the polymer cement mortar 50 is applied before the water-based epoxy primer 20 hardens.
[0119] By the mortar application step, a binder layer 52 made of polymer cement mortar 50 is formed on the reinforced surface 90A (specifically, on the surface of the primer layer 22) of the structure 90 to which the water-based epoxy primer 20 has been applied. The thickness of the binder layer 52 is at least thicker than the fiber-reinforced sheet 40, for example, about 2 mm to 10 mm.
[0120] <Adhesion process> The adhesion step is a step in which, before the applied polymer cement mortar 50 hardens, the fiber reinforced sheet 40 is pressed against the applied layer of polymer cement mortar 50 to embed it and adhere it to the reinforced surface 90A of the structure 90. As a result, the fiber reinforced sheet 40 is disposed inside the binder layer 52 of the polymer cement mortar 50.
[0121] The fiber reinforced sheet 40 is pressed with a roller or a rubber spatula, so that the air layer at the adhesive interface is expelled from the gaps between the fiber reinforced plastic strands 43, and the fiber reinforced sheet 40 is embedded and adhered to the binder layer 52.
[0122] <Reinforcement structure 10> 1, a reinforcement structure 10 is constructed, which includes a primer layer 22 disposed on the surface of a structure 90, a binder layer 52 disposed on the surface of the primer layer 22, and a fiber-reinforced sheet 40 embedded inside the binder layer 52. Furthermore, in the reinforcement structure 10, the binder layer 52 has a mixture layer 29 at the boundary (interface) with the primer layer 22, in which the water-based epoxy primer 20 and polymer cement mortar 50 are mixed. The miscible layer 29 is formed, for example, by satisfying at least the following conditions (1) to (3). (1) The water-based epoxy primer 20 is a two-component type consisting of a base agent and a curing agent, and the curing agent is water-soluble. (2) Applying the polymer cement mortar 50 when the coating film of the water-based epoxy primer 20 is in the early stage of polymerization and contains more than 10 wt % moisture. (3) The water-based epoxy primer 20 before hardening and the polymer cement mortar 50 before hardening have an affinity to be mixed with each other.
[0123] Specifically, the miscible layer 29 is formed on the binder layer 52 side of the interface between the primer layer 22 and the binder layer 52. Here, the miscible layer 29 is a layer in which the epoxy resin component of the water-based epoxy primer 20 is mixed and integrated with the polymer cement mortar 50, and it is presumed that the epoxy resin component of the primer 20 bonds with the calcium hydroxide in the polymer cement mortar 50, thereby strengthening the adhesion between the primer layer and the polymer cement layer.
[0124] When the cross-section of the applied area is observed using, for example, an SEM-EPMA (electron probe microanalyzer) or SEM-EDX (energy dispersive X-ray spectroscopy, also known as SEM-EDS), the mixed layer 29 can be observed as a layer approximately 10 to 50 μm thick in which the distribution of carbon derived from the water-based epoxy primer 20 and the distribution of calcium derived from the polymer cement mortar 50 overlap.
[0125] As described above, the mixed layer 29 is formed so that the primer layer 22 is mixed with the binder layer 52, and therefore the distribution of carbon derived from the primer is observed to decrease continuously from the primer layer 22 toward the binder layer 52, but since the base (the reinforced surface 90A of the structure 90) is a rough surface having irregularities, the primer layer 22 is also likely to have localized unevenness. For this reason, the primer layer 22, the binder layer 52, and the mixed layer 29 are not necessarily observed in a uniform state over the entire surface of the primer layer 22 and the binder layer 52, and the primer layer 22 and the mixed layer 29 cannot be clearly distinguished, and it may be observed as if only the mixed layer 29 exists.
[0126] <Effects of this embodiment> The effects of this embodiment will be described.
[0127] In the reinforcing method according to this embodiment, fiber-reinforced sheet 40 is formed by adhering inorganic powder to the outer periphery of multiple fiber-reinforced plastic strands 43, and the inorganic powder bites into the binder, providing an anti-slip effect that enhances adhesion between fiber-reinforced sheet 40 and polymer cement mortar 50. This makes it possible to prevent fiber-reinforced sheet 40 from peeling off from the binder before it breaks or before the polymer cement mortar experiences cohesive failure, without using a hazardous material under the Fire Service Act (the joint adhesive in Patent Document 3).
[0128] Here, since the fiber-reinforced sheet 40 is a sheet in which multiple fiber-reinforced plastic strands 43 are aligned in a curtain-like shape in the longitudinal direction, when inorganic powder is adhered to the outer periphery of the multiple fiber-reinforced plastic strands 43, the spaces between the multiple fiber-reinforced plastic strands 43 become narrower.
[0129] In contrast, in the reinforcing method according to the present embodiment, polymer cement mortar 50 has a flow value of 140 mm or more in the JIS flow test, so that polymer cement mortar 50 has high fluidity, and when fiber reinforced sheet 40 is pressed against a coating layer of polymer cement mortar 50 to embed it, fiber reinforced plastic wires 43 of fiber reinforced sheet 40 can easily pass through narrow gaps between them. As a result, poor construction (poor adhesion between fiber reinforced sheet 40 and the binder) is suppressed, and fiber reinforced sheet 40 can be prevented from peeling off from the binder before it breaks.
[0130] Furthermore, since the flow value of polymer cement mortar 50 in the JIS flow test is 180 mm or less and the sagging amount in JHS-416-2004, Sectional Repair Material Quality Standard Test Method, is 10 mm or less, polymer cement mortar 50 applied to the surface of structure 90 is prevented from falling off from the surface.
[0131] Furthermore, polymer cement mortar 50 had a tensile strength of 2.5 N / mm2 in a uniaxial direct tensile strength test at 28 days. 2The tensile stress at a tensile strain of 1.5% in the test is 35% or more of the tensile strength.
[0132] For this reason, even if tensile stress occurs in fiber reinforced sheet 40 due to deflection of structure 90, polymer cement mortar 50 is less likely to crack (break), and fiber reinforced sheet 40 can be prevented from peeling off from the binder before breaking.
[0133] In the reinforcing method according to the present embodiment, as described above, polymer cement mortar 50 contains 0.9 to 1.5 vol % reinforcing organic fiber, so that polymer cement mortar 50 is less likely to crack (fracture), and the viscosity of polymer cement mortar 50 is maintained low, allowing polymer cement mortar 50 to easily pass between fiber reinforced plastic wires 43 of fiber reinforced sheet 40. As a result, poor application (poor adhesion between fiber reinforced sheet 40 and the binder) is suppressed, and fiber reinforced sheet 40 is prevented from peeling off from the binder before breaking.
[0134] In the reinforcing method according to the present embodiment, as described above, the reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of 6 to 12 mm and an aspect ratio of 120 to 1200, so that polymer cement mortar 50 is less likely to crack (fracture), and the viscosity of polymer cement mortar 50 is maintained low, allowing polymer cement mortar 50 to easily pass between fiber-reinforced plastic wires 43 of fiber-reinforced sheet 40. As a result, poor application (poor adhesion between fiber-reinforced sheet 40 and the binder) is suppressed, and fiber-reinforced sheet 40 is prevented from peeling off from the binder before breaking.
[0135] In the reinforcing method according to the present embodiment, as described above, polymer cement mortar 50 contains fine aggregate having a maximum diameter of 0.2 to 1.2 mm and a fine particle size (FM) value of 0.5 to 2.3, so that the viscosity of polymer cement mortar 50 is kept low and the maximum diameter of the fine aggregate is kept small, allowing polymer cement mortar 50 to easily pass between fiber-reinforced plastic wires 43 of fiber-reinforced sheet 40. As a result, poor construction (poor adhesion between fiber-reinforced sheet 40 and the binder) is suppressed, and fiber-reinforced sheet 40 is prevented from peeling off from the binder before breaking.
[0136] Furthermore, in the reinforcement method according to this embodiment, as described above, the spacing between the fiber-reinforced plastic strands 43 in the fiber-reinforced sheet 40 is more than 3 mm and not more than 10 mm, so that polymer cement mortar 50 can easily pass between the fiber-reinforced plastic strands 43 in the fiber-reinforced sheet 40 while suppressing a decrease in the reinforcing effect.
[0137] As a result, poor application (poor adhesion between the fiber reinforced sheet 40 and the binder) is suppressed, and the fiber reinforced sheet 40 is prevented from peeling off from the binder before it breaks.
[0138] In the reinforcing method according to the present embodiment, as described above, the inorganic powder attached to the fiber-reinforced sheet 40 has an average particle size of 0.900 mm or less and is concentrated in a range of 400 to 2000 g / m 2 per unit area of the fiber-reinforced sheet 40. 2 Because the inorganic powder is attached, the anti-slip effect maintains high adhesion between fiber reinforced sheet 40 and polymer cement mortar 50, making it easier for polymer cement mortar 50 to pass between fiber reinforced plastic wires 43 of fiber reinforced sheet 40.
[0139] As a result, poor application (poor adhesion between the fiber reinforced sheet 40 and the binder) is suppressed, and the fiber reinforced sheet 40 is prevented from peeling off from the binder before it breaks.
[0140] Furthermore, in the reinforcement method according to the present embodiment, as described above, the ratio of the diameter of the fiber reinforced plastic wires 43 in the fiber reinforced sheet 40, the spacing between the fiber reinforced plastic wires 43, and the diameter of the inorganic powder is 1:0.5-5:0.03-1, so that the anti-slip effect of the inorganic powder maintains high adhesion between the fiber reinforced sheet 40 and the polymer cement mortar 50, and makes it easy for the polymer cement mortar 50 to pass between the fiber reinforced plastic wires 43 in the fiber reinforced sheet 40.
[0141] As a result, poor application (poor adhesion between the fiber reinforced sheet 40 and the binder) is suppressed, and the fiber reinforced sheet 40 is prevented from peeling off from the binder before it breaks.
[0142] Furthermore, in the reinforced structure 10 according to this embodiment, a mixture layer 29 in which the water-based epoxy primer 20 and the polymer cement mortar 50 are mixed is provided at the boundary (interface) between the primer layer 22 and the binder layer 52. It is presumed that the calcium component of the polymer cement mortar 50 and the epoxy component of the water-based epoxy primer are bonded in the mixture layer 29, and therefore the adhesion between the water-based epoxy primer 20 and the polymer cement mortar 50 is improved.
[0143] As described above, when the cross section of the applied area is observed using, for example, SEM-EPMA (electron probe microanalyzer) or SEM-EDX (energy dispersive X-ray spectroscopy), the mixed layer 29 can be observed as a layer approximately 10 to 50 μm thick in which the distribution of carbon derived from the water-based epoxy primer and the distribution of calcium derived from the polymer cement mortar 50 overlap.
[0144] As a result, the adhesion between reinforced surface 90A of structure 90 and polymer cement mortar 50 is improved, and fiber reinforced sheet 40 is prevented from peeling off from reinforced surface 90A together with the binder before breaking.
[0145] <Evaluation test> In this test, the reinforcing effect of the reinforcing method according to the present embodiment was evaluated. Specifically, in this test, Examples 1 to 9 and Comparative Examples 1 to 17 were evaluated as follows.
[0146] [JIS flow test] The test was carried out in accordance with JIS A 1171 test method for polymer cement mortar.
[0147] [One-way shear test] In this test, a one-way shear test was carried out using a JIS concrete slab (corresponding to structure 90), a fiber-reinforced sheet 40, a water-based epoxy primer 20, and a polymer cement mortar 50.
[0148] The reinforcing effect of the fiber-reinforced sheet 40 on a concrete body (corresponding to structure 90) has been confirmed when the fiber-reinforced sheet 40 itself is used for reinforcement using conventional epoxy resin. Here, the reinforcing effect was confirmed by evaluating the adhesion performance between the fiber-reinforced sheet and the concrete body when a non-hazardous material, which differs from the conventional construction method, was used by a one-way tensile shear test.
[0149] The test piece 100 for the single-sided shear test was prepared by applying water-based epoxy primer 20 to a JIS concrete flat plate 90 of 30 cm square after scraping, applying polymer cement mortar 50 in 3 rows with a thickness of 5 mm in a width of 4 cm, embedding fiber reinforced sheet 40 cut to a width of 4 cm and a length of 60 cm in 3 rows so that one side protrudes, and then curing in a 20°C environment for 2 weeks, and bonding a tab 99 made of epoxy resin and an aramid fiber sheet to one end of the fiber reinforced sheet 40 (see FIG. 7). The single-sided shear test was performed on the test piece 100 using a universal testing machine and a test piece fixing jig 102 as shown in FIG. 8, and evaluating the fracture load and fracture mode, and the evaluation of the integrity of the fiber reinforced sheet and the concrete member was performed with n=3. The criteria for judging pass / fail were based on the measured peel fracture energy Gf and observation of the fracture mode, with the former being 0.5 N / m and the latter being that no "bond break between the fiber-reinforced sheet (CFSS) and the bonding material (PCM)" was observed in any of the test pieces.
[0150] [Workability test of polymer cement mortar 50] As a test for evaluating the workability of the polymer cement mortar 50, the polymer cement mortar 50 was applied to a concrete slab simulating a ceiling surface in an area of 100 mm wide x 250 mm long or more and 5 mm thick, and a fiber reinforced sheet 40 cut to 50 mm wide x 200 mm long was examined to determine whether it could be embedded using a plastering trowel and a wallpaper roller. That is, the fiber reinforced sheet 40 was placed on the polymer cement mortar 50 applied to a thickness of 5 mm, and pressed with a wallpaper roller to cause the polymer cement mortar 50 to seep out from between the fiber reinforced sheet 40, and the seeped polymer cement mortar 50 was covered with a plastering trowel to be smoothed over the fiber reinforced sheet 40, and an evaluation was made as to whether it was possible to evaluate (hereinafter, sometimes abbreviated as a ceiling surface application test).
[0151] <Examples 1 to 4 and Comparative Examples 1 to 10> [Polymer Cement Mortar 50] In Examples 1 to 4 and Comparative Examples 1 to 10, in order to examine the range of application of polymer cement mortar 50, polymer cement mortar 50 was produced based on Refremolset D manufactured by Sumitomo Osaka Cement Co., Ltd., with the amount of reinforcing fiber, the length of reinforcing fiber, the aspect ratio of the fiber (ratio of fiber diameter to length), the type of fiber, and the amount of water added adjusted, and basic physical properties of the mortar such as JIS flow, tensile strength, and tensile stress retention (the ratio of tensile stress at a tensile strain of 1.5% to the tensile strength) were evaluated, followed by carrying out a single-sided shear test using a JIS plate and a fiber-reinforced sheet 40. As the reinforcing organic fiber contained in polymer cement mortar 50, high-strength polyethylene fiber was used in Examples 1 to 4 and Comparative Examples 1, 2, 4, and 6 to 10, nylon fiber was used in Comparative Example 3, and vinylon fiber was used in Comparative Example 5.
[0152] [Water-based epoxy primer 20] FP Primer FP-EE from Nippon Steel Chemical & Material Co., Ltd. was used as the water-based epoxy primer 20. This primer is a two-part type consisting of a base agent and a curing agent.
[0153] [Fiber reinforced sheet 40] As the fiber reinforced sheet 40, FSS-MM-450ME (S6) and FSS-MM-450ME (C1) manufactured by Nippon Steel Chemical & Material Co., Ltd. were used. FSS-MM-450ME(S6) is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 More than 4.0×105N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires are spaced about 8 mm apart, and the gap between the wires is about 5.4 mm. The fiber-reinforced sheet is covered with 1 m of No. 6 silica sand (average particle size 0.294 mm). 2 The fiber reinforced sheet is attached using an epoxy resin adhesive at a ratio of 1 kg per unit area. FSS-MM-450ME(C1) is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires are installed at intervals of about 8 mm, and the gaps between the wires are about 5.4 mm. The fiber-reinforced sheet is fitted with 1 rin of crushed white dragon stone (average grain size 0.4 mm) for 1 m. 2 The fiber reinforced sheet is attached using an epoxy resin adhesive at a ratio of 1 kg per unit area.
[0154] [Creating test specimens] The base agent and hardener of the water-based epoxy primer 20 were mixed in a weight ratio of 100:100, thoroughly mixed, and then applied at 0.15 kg / m to a scraped JIS concrete slab 90. 2 After drying for 30 minutes in a temperature environment of 20° C., the fiber reinforced sheet 40 was attached with a plastering trowel using the polymer cement mortar 50. The combined thickness of the fiber reinforced sheet 40 and the polymer cement mortar 50 was 5 mm.
[0155] [Example 1] In Example 1, mortar was mixed with 1.1 wt% high-strength polyethylene reinforcing fiber with a length of 9 mm and an aspect ratio of 750, a maximum diameter of fine aggregate of 0.45 mm, an FM value of 1.02, and a W / P of 22.0 wt%. The JIS flow of this mortar was 160 mm, the drip length (amount of drip) was 5 mm in a drip test based on JHS-416-2004 Sectional Repair Material Quality Standard Test Method (hereinafter abbreviated as JHS method), and the tensile strength after 28 days of curing at 20°C was 3.69 N / mm 2 , the tensile stress at 1.5% strain is 3.08N / mm 2 The tensile stress retention rate was 83.5%. In a ceiling application test using this mortar and FSS-MM-450ME(C1), the mortar seeped out well and passed the test without dripping. The results of the single-sided shear test after four weeks of curing in a 20°C environment showed that the average fracture load was 19.8 kN, the peel fracture energy Gf was 1.06 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0156] [Example 2] In Example 2, 1.1 wt% of high-strength polyethylene reinforcing fibers with a length of 9 mm and an aspect ratio of 750 were added, and a mortar was mixed with fine aggregates having a maximum diameter of 1.20 mm, an FM value of 2.01, and a W / P ratio of 19.8 wt%. The JIS flow of this mortar was 157 mm, the drip length according to the JHS method was 5 mm, and the tensile strength after curing for 28 days at 20°C was 4.18 N / mm 2 , the tensile stress at 1.5% strain is 1.73N / mm 2 The tensile stress retention rate was 41.4%. In a ceiling application test using this mortar and FSS-MM-450ME(S6), the mortar seeped out well and passed the test without dripping. The results of the single-sided shear test after four weeks of curing in a 20°C environment showed that the average fracture load was 20.0 kN, the peel fracture energy Gf was 1.09 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0157] [Example 3] In Example 3, 0.9 wt% of high-strength polyethylene reinforcing fibers with a length of 9 mm and an aspect ratio of 750 were added, and mortar was mixed with fine aggregates having a maximum diameter of 0.45 mm, an FM value of 1.02, and a W / P ratio of 22.0 wt%. The JIS flow of this mortar was 167 mm, the sagging length according to the JHS method was 6 mm, and the tensile strength after curing for 28 days at 20°C was 3.64 N / mm 2 , the tensile stress at 1.5% strain is 2.77N / mm 2 The tensile stress retention rate was 76.1%. In a ceiling application test using this mortar and FSS-MM-450ME(S6), the mortar seeped out well and passed the test without dripping. The results of the single-sided shear test after four weeks of curing at 20°C showed that the average fracture load was 14.5kN, the peel fracture energy Gf was 0.57N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0158] [Example 4] In Example 4, 1.5 wt% of high-strength polyethylene reinforcing fibers with a length of 9 mm and an aspect ratio of 750 were added, and a mortar was mixed with fine aggregates having a maximum diameter of 0.45 mm, an FM value of 1.02, and a W / P ratio of 23.0 wt%. The JIS flow of this mortar was 150 mm, the drip length according to the JHS method was 4 mm, and the tensile strength after curing for 28 days at 20°C was 4.48 N / mm 2 , the tensile stress at 1.5% strain is 3.38N / mm 2 The tensile stress retention rate was 75.4%. In a ceiling application test using this mortar and FSS-MM-450ME(S6), the mortar seeped out well and passed the test without dripping. The results of the single-sided shear test after four weeks of curing in a 20°C environment showed that the average fracture load was 13.6 kN, the peel fracture energy Gf was 0.50 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0159] [Comparative Example 1] In Comparative Example 1, the composition was the same as in Example 1, except that 0.7 wt% of high-strength polyethylene reinforcing fibers with a length of 9 mm and an aspect ratio of 750 were added. The JIS flow of this mortar was 177 mm, the drip length according to the JHS method was 8 mm, and the tensile strength after curing for 28 days at 20°C was 3.16 N / mm 2 , the tensile stress at 1.5% strain is 0.90N / mm 2 The tensile stress retention rate was 28.5%. In a ceiling application test using this mortar and FSS-MM-450ME(S6), the mortar seeped out well and passed the test with no dripping. However, in a single-sided shear test after curing for 4 weeks in a 20°C environment, the average breaking load was 12.0 kN, the peeling fracture energy Gf was 0.39 N / mm, and the fracture mode was that the mortar itself cracked early after the load was applied, causing the surface to separate from the fiber-reinforced sheet.
[0160] [Comparative Example 2] In Comparative Example 2, the composition was the same as in Example 1, except that 2.0 wt% of high-strength polyethylene reinforcing fibers with a length of 9 mm and an aspect ratio of 750 were added. During mixing, the fiber clumps did not disperse completely and remained as clumps, making it impossible to handle as mortar. Subsequent evaluations were not performed.
[0161] [Comparative Example 3] In Comparative Example 3, 1.1 wt% of nylon reinforcing fiber with a length of 5 mm and an aspect ratio of 179 was added, and the W / P was changed to 19.0, but the mix was the same as in Example 1. The JIS flow of this mortar was 167 mm, the drip length according to the JHS method was 6 mm, and the tensile strength after curing for 28 days at 20°C was 1.10 N / mm 2 , the tensile stress at 1.5% strain is 0.32N / mm 2 The tensile stress retention rate was 29.1%. In a ceiling application test using this mortar and FSS-MM-450ME(S6), the mortar seeped out well and passed the test with no dripping. However, in the results of a one-way shear test after curing for 4 weeks in a 20°C environment, the average breaking load was 8.0kN, the peeling fracture energy Gf was 0.17N / mm, and the fracture mode was that the mortar itself cracked early after the load was applied, resulting in fracture of the fibers in the mortar.
[0162] [Comparative Example 4] In Comparative Example 4, the composition was the same as in Example 1, except that 1.1 wt% of high-strength polyethylene reinforcing fibers with a length of 15 mm and an aspect ratio of 1250 were added. When mixing this mortar, the viscosity of the mortar increased too much after the fibers were added, causing the agitator motor to trip, and the fiber clumps were not dispersed completely and formed large clumps, making it impossible to handle as mortar. Subsequent evaluations were not performed.
[0163] [Comparative Example 5] In Comparative Example 5, 1.1 wt% of vinylon reinforcing fiber with a length of 12 mm and an aspect ratio of 60 was added, and the W / P was changed to 19.0, but the mix was the same as in Example 1. The JIS flow of this mortar was 176 mm, the drip length according to the JHS method was 8 mm, and the tensile strength after curing for 28 days at 20°C was 1.40 N / mm 2 , the tensile stress at 1.5% strain is 0.32N / mm 2 The tensile stress retention rate was 31.4%. In a ceiling application test using this mortar and FSS-MM-450ME(S6), the mortar seeped out well and passed the test with no dripping. However, in the results of a one-way shear test after curing for 4 weeks in a 20°C environment, the average breaking load was 12.2kN, the peeling fracture energy Gf was 0.40N / mm, and the fracture mode was that the mortar itself cracked early after the load was applied, resulting in fracture of the fibers in the mortar.
[0164] [Comparative Example 6] In Comparative Example 6, the composition was the same as in Example 1, except that the maximum diameter of the fine aggregate was 0.15 mm and the coarse aggregate ratio (FM value) was 0.03. The viscosity of this mortar increased too much after the fibers were added during mixing, making it impossible to mix uniformly, and it was impossible to handle it as mortar. Subsequent evaluations were not performed.
[0165] [Comparative Example 7] In Comparative Example 7, the mix was the same as in Example 1, except that the maximum diameter of the fine aggregate was 1.75 mm and the coarse aggregate ratio (FM value) was 3.54. The JIS flow of this mortar was 161 mm, and the drip length according to the JHS method was 5 mm. In a ceiling application test, this mortar did not seep out from the gaps between the mortar wires when the fiber reinforced sheet was applied, and application was not sufficient.
[0166] [Comparative Example 8] In Comparative Example 8, the maximum diameter of the fine aggregate was 1.20 mm, the same as in Example 2, but the coarse aggregate ratio (FM value) was 2.91. The rest of the mix was the same as in Example 1. The JIS flow of this mortar was 162 mm, and the drip length according to the JHS method was 5 mm. This mortar had too high a viscosity, and in the ceiling surface construction test, the mortar did not seep out much from the gaps between the wires when the fiber-reinforced sheet was constructed, and construction was not sufficient.
[0167] [Comparative Example 9] In Comparative Example 9, the mix was the same as in Example 1, except that the W / P value was 18.5. The JIS flow value of this mortar was 128 mm. This mortar also had too high a viscosity, and in the ceiling application test, the mortar did not seep out from the gaps between the wires when the fiber-reinforced sheet was applied, and sufficient application was not possible.
[0168] [Comparative Example 10] In Comparative Example 10, the mix was the same as in Example 1, except that the W / P value was 25.5. The JIS flow value of this mortar was 183 mm. This mortar failed the JHS dripping test because all the mortar flowed away, and in the ceiling application test, the viscosity was too low to allow it to be applied to the ceiling surface in a thickness of 5 mm.
[0169] [Test results of Examples 1 to 4 and Comparative Examples 1 to 10] The test results of Examples 1 to 4 and Comparative Examples 1 to 10 are shown in Table 1 in Fig. 9. As shown in Table 1, in Examples 1 to 4, the peel fracture energy calculated from the results of the single-side tensile shear test was 0.5 N / mm or more, and was better than Comparative Examples 1 to 10, confirming the reinforcing effect.
[0170] <Examples 5 to 9 and Comparative Examples 11 to 17> In Examples 5 to 9 and Comparative Examples 11 to 17, in order to examine the application range of the fiber reinforced sheet 40 and the water-based epoxy primer 20, one-way pull shear tests were carried out by changing the fiber reinforced sheet 40 and the water-based epoxy primer 20 used in the tests. As the polymer cement mortar 50, the polymer cement mortar 50 in the above-mentioned Example 1 was used.
[0171] [Example 5] In Example 5, a test piece was prepared under the same conditions as in Example 1, except that the fiber-reinforced sheet used was FSS-MM-450ME(S4) manufactured by Nippon Steel Chemical & Material Corporation. FSS-MM-450ME(S4) is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires are spaced about 8 mm apart, and the gap between the wires is about 5.4 mm. The fiber-reinforced sheet is covered with 1 m of No. 4 silica sand (average particle size 0.887 mm). 2 The fiber reinforced sheet is attached using an epoxy resin adhesive at a ratio of 1 kg per unit area. As shown in FIG. 6, the spacing between the wires is the spacing (distance) S3 between the centers of the fiber-reinforced plastic wires 43, and the gap between the wires is the gap S2 between the fiber-reinforced plastic wires 43 without considering the inorganic powder. Also, the "sand-attached CFSS gap" shown in FIG. 10 indicates the gap S1 between the wires with the inorganic powder attached (the gap S1 between the wires containing the inorganic powder) (see FIG. 6). In FIG. 6, the diameter of the fiber-reinforced plastic wire 43 is indicated by the diameter D2, and the diameter of the inorganic powder is indicated by the diameter D1. FIG. 6 is a diagram showing the fiber-reinforced plastic wire 43 and the inorganic powder, and in reality, the inorganic powder is attached to the outer periphery of the fiber-reinforced plastic wire 43. In a ceiling application test using this mortar, the mortar seeped out well and passed the test without dripping. In addition, the results of the single-sided shear test after four weeks of curing in a 20°C environment showed that the average fracture load was 26.1 kN, the peel fracture energy Gf was 1.90 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0172] [Example 6] In Example 6, a test piece was prepared under the same conditions as in Example 1, except that the fiber-reinforced sheet used was FSS-MM-700ME (S6) manufactured by Nippon Steel Chemical & Material Co., Ltd. A test piece was prepared under the same conditions as in Example 1. FSS-MM-700ME(S6) is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 More than 4.0×105N / mm 2 So, 1m 2 Carbon fiber usage per unit is 700g / m 2 The wires are spaced about 5 mm apart, and the gap between the wires is about 3.0 mm. The fiber-reinforced sheet is covered with 1 m of No. 6 silica sand (average particle size 0.294 mm). 2 The fiber reinforced sheet is attached using an epoxy resin adhesive at a ratio of 1 kg per unit area. In a ceiling application test using this mortar, the mortar seeped out well and passed the test without dripping. In addition, the results of the single-sided shear test after four weeks of curing in a 20°C environment showed that the average fracture load was 19.4 kN, the peel fracture energy Gf was 1.02 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0173] [Example 7] In Example 7, a test piece was prepared under the same conditions as in Example 1, except that the fiber-reinforced sheet used was FSS-MM-300ME (S6) manufactured by Nippon Steel Chemical & Material Corporation. FSS-MM-300ME(S6) is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 300g / m 2 The wires are installed at intervals of about 12 mm, and the gap between the wires is about 10.0 mm. The fiber-reinforced sheet is covered with 1 m of No. 6 silica sand (average particle size 0.294 mm). 2 The fiber reinforced sheet is attached using an epoxy resin adhesive at a ratio of 1 kg per unit area. In a ceiling application test using this mortar, the mortar seeped out well and passed the test without dripping. In addition, the results of the single-sided shear test after four weeks of curing in a 20°C environment showed that the average fracture load was 20.3 kN, the peel fracture energy Gf was 1.13 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0174] [Example 8] In Example 8, a test piece was prepared under the same conditions as in Example 1, except that the fiber-reinforced sheet used was FSS-MM-450ME (S6 / A4) manufactured by Nippon Steel Chemical & Material Corporation. FSS-MM-450ME (S6 / A4) has a carbon fiber equivalent cross-sectional area of 2.0 mm for one wire. 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires are spaced about 8 mm apart, and the gap between the wires is about 5.4 mm. The fiber-reinforced sheet is covered with 1 m of No. 6 silica sand (average particle size 0.294 mm). 2 The fiber reinforced sheet is attached using an epoxy resin adhesive at a ratio of 400 g per sheet. In a ceiling application test using this mortar, the mortar seeped out well and passed the test without dripping. In addition, the results of the single-sided shear test after four weeks of curing in a 20°C environment showed that the average fracture load was 19.9 kN, the peel fracture energy Gf was 1.08 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0175] [Example 9] In Example 9, a test piece was prepared and tested under the same conditions as in Example 1, except that FSS-MM-450(S8) manufactured by Nippon Steel Chemical & Material Co., Ltd. was used as the fiber-reinforced sheet. FSS-MM-450(S8) has a carbon fiber equivalent cross-sectional area of 2.0 mm for one wire. 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires were installed at intervals of about 8 mm, and the gaps between the wires were about 5.4 mm. The fiber-reinforced sheet was covered with 1 m of No. 8 silica sand (average particle size 0.073 mm). 2 It is a fiber-reinforced sheet attached at a ratio of 1 kg per unit area. The results of the single-sided shear test of the test pieces showed that the average fracture load was 23.4 N, the peel fracture energy Gf was 1.49 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.
[0176] [Comparative Example 11] In Comparative Example 11, a test piece was prepared and subjected to the test under the same conditions as in Example 1, except that FSS-MM-450 (S3) manufactured by Nippon Steel Chemical & Material Co., Ltd. was used as the fiber-reinforced sheet. FSS-MM-450(S3) is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires were installed at intervals of about 8 mm, and the gaps between the wires were about 5.4 mm. The fiber-reinforced sheet was covered with 1 m of No. 3 silica sand (average particle size 1.344 mm). 2 It is a fiber-reinforced sheet attached at a ratio of 1 kg per unit area. In the single-sided shear test specimen using this fiber-reinforced sheet, the mortar itself did not pass through the fiber-reinforced sheet, and when the mortar hardened, it separated at the fiber-reinforced sheet, making it unsuitable for testing.
[0177] [Comparative Example 12] In Comparative Example 12, a test piece was prepared and subjected to the test under the same conditions as in Example 1, except that FSS-MM-450 (S6) manufactured by Nippon Steel Chemical & Material Co., Ltd. was used as the fiber-reinforced sheet. FSS-MM-450(S6) is a fiber-reinforced sheet that is reinforced using ordinary epoxy resin. The cross-sectional area of one wire is 0.66 mm 2 The average cross-sectional diameter of the wire, including the resin, is 1.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires were installed at intervals of about 2.7 mm, and the gaps between the wires were about 1.3 mm. The fiber-reinforced sheet was covered with 1 m of No. 6 silica sand (average particle size 0.294 mm). 2 It is a fiber-reinforced sheet attached at a ratio of 1 kg per unit area. In the single-sided shear test specimen using this fiber-reinforced sheet, the mortar itself did not pass through the fiber-reinforced sheet, and when the mortar hardened, it separated at the fiber-reinforced sheet, making it unsuitable for testing.
[0178] [Comparative Example 13] In Comparative Example 13, a test piece was prepared and subjected to the test under the same conditions as in Example 1, except that FSS-MM-450 (S3) manufactured by Nippon Steel Chemical & Material Co., Ltd. was used as the fiber-reinforced sheet. FSS-MM-450(S3) is a fiber-reinforced sheet that is reinforced using ordinary epoxy resin. The cross-sectional area of one wire is 0.66 mm 2 The average cross-sectional diameter of the wire, including the resin, is 1.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 The wires are spaced 2.7 mm apart, and the gap between the wires is 1.3 mm. The fiber-reinforced sheet is covered with 1 m of No. 3 silica sand (average particle size 1.344 mm). 2 It is a fiber-reinforced sheet attached at a ratio of 1 kg per unit area. In the single-sided shear test specimen using this fiber-reinforced sheet, the mortar itself did not pass through the fiber-reinforced sheet, and when the mortar hardened, it separated at the fiber-reinforced sheet, making it unsuitable for testing.
[0179] [Comparative Example 14] In Comparative Example 14, a test piece was prepared and subjected to the test under the same conditions as in Example 1, except that FSS-MM-180ME (S6) manufactured by Nippon Steel Chemical & Material Co., Ltd. was used as the fiber-reinforced sheet. FSS-MM-180ME(S6) is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 180g / m 2 The wires were installed at intervals of about 19 mm, and the gaps between the wires were about 16.8 mm. The fiber-reinforced sheet was covered with 1 m of No. 6 silica sand (average particle size 0.294 mm). 2 It is a fiber-reinforced sheet attached at a ratio of 1 kg per unit area. The results of the one-way tensile shear test of the test piece showed that the average fracture load was 11.2 N, the peel fracture energy Gf was 0.34 N / mm, and the fracture mode was breakage of the carbon fiber.
[0180] [Comparative Example 15] In Comparative Example 15, a test piece was prepared and tested under the same conditions as in Example 1, except that FSS-MM-450ME (S6 / A10) manufactured by Nippon Steel Chemical & Material Co., Ltd. was used as the fiber-reinforced sheet. FSS-MM-450ME (S6 / A10) has a carbon fiber equivalent cross-sectional area of 2.0 mm for one wire. 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m2 The wires were installed at intervals of about 8 mm, and the gaps between the wires were about 5.4 mm. The fiber-reinforced sheet was covered with 1 m of No. 6 silica sand (average particle size 0.294 mm). 2 It is a fiber-reinforced sheet with 100g attached per unit area. The results of the one-way tensile shear test on the test specimens showed that the average fracture load was 22.6 N, the peel fracture energy Gf was 1.40 N / mm, and the fracture mode in some of the test specimens was NG mode, that is, interfacial failure ("CFSS / PCM adhesion failure") in which the wire was pulled out of the mortar.
[0181] [Comparative Example 16] In Comparative Example 16, a test piece was prepared and subjected to the test under the same conditions as in Example 1, except that FSS-MM-450ME manufactured by Nippon Steel Chemical & Material Corporation was used as the fiber-reinforced sheet. FSS-MM-450ME is a single wire with a carbon fiber equivalent cross-sectional area of 2.0 mm 2 The average cross-sectional diameter of the wire, including the resin, is 2.2 mm, and the tensile strength of the wire converted to the cross-sectional area of carbon fiber is 2900 N / mm 2 The elastic modulus is 4.0×10 5 N / mm 2 So, 1m 2 Carbon fiber usage per unit is 450g / m 2 It is a fiber-reinforced sheet with the wires installed at intervals of approximately 8 mm and the gaps between the wires being approximately 5.4 mm. Instead of applying inorganic powder, a water-based epoxy primer is applied directly to the fiber-reinforced sheet. 2 After drying for 30 minutes in a 20°C environment, a ceiling application test was performed in the same manner as in Example 1, and a single-sided shear test specimen was prepared and a single-sided shear test was performed in the same manner as in Example 1. The ceiling construction test was carried out without any problems, and the results of the one-sided shear test on the test specimens showed that the average fracture load was 25.1N and the peel fracture energy Gf was 1.71N / mm. However, the fracture mode in all test specimens was NG mode, that is, interfacial fracture ("CFSS / PCM bond failure") in which the wire was pulled out of the mortar.
[0182] [Comparative Example 17] In Comparative Example 17, an acrylic water-based emulsion was used as a primer at 0.15 kg / m 2 Test pieces were prepared under the same conditions as in Example 1, except for the coating, and subjected to the test. Lionbond, a one-component water-based acrylic emulsion, is a water-based primer commonly used for mortar joints. The results of the single-sided tensile shear test of the test specimens showed that the average fracture load was 11.2 N, the peel fracture energy Gf was 0.34 N / mm, and the fracture mode was cohesive failure of the primer itself applied to the JIS concrete slab.
[0183] [Test results of Examples 5 to 9 and Comparative Examples 11 to 17] The test results of Examples 5 to 9 and Comparative Examples 11 to 17 are shown in Table 2 in Fig. 10. As shown in Table 2, in Examples 5 to 9, the peel fracture energy calculated from the results of the single-side shear test was 0.5 N / mm or more, which is better than Comparative Examples 11 to 17, and in addition, there were no test pieces that showed interface fracture ("CFSS / PCM bond failure") in which the wires of the strand sheet were pulled out of the mortar, confirming that there was a sufficient reinforcing effect.
[0184] In Comparative Examples 15 and 16, the peel fracture energy exceeded 0.5 N / mm even though the fracture mode was NG mode, but this was due to the frictional force between the fiber-reinforced sheet 40 and the peeled inorganic powder and binder. Therefore, in cases where a dynamic load is applied, such as a wheel load running test described later, the fiber-reinforced sheet 40 easily peels off from the binder before breaking, resulting in NG.
[0185] Furthermore, the interface of the primer and binder coating areas in Example 1 and Comparative Example 17 was observed and analyzed using an SEM-EDSX (JSM-IT500HR scanning electron microscope manufactured by JEOL Ltd.) at a voltage of 10 kV and observation mode of backscattered electron image. Mapping of the elements Si, C, and Ca was performed, and it was confirmed that in Example 1, a mixed layer was formed by overlapping the C in the primer layer and the Ca in the binder layer, and that the abundance ratio of the C element in the mixed layer was about 10% higher than that in the binder layer, but in Comparative Example 17, no overlapping of the C in the primer layer and the Ca in the binder layer was observed.
[0186] <Deck wheel load running test> In order to finally confirm the reinforcing effect of the reinforcing method according to this embodiment, a wheel load running test was carried out using a full-scale concrete deck specimen (see Figures 12 and 13) with reference to the following existing literature.
[0187] Previous literature: Okada et al., "Effect of deck reinforcement using lattice-arranged carbon fiber sheets," Proceedings of the 3rd Road Bridge Deck Symposium, pp175-180
[0188] This test, as shown in Figure 11, is a test method for evaluating the fatigue durability of a deck by applying a load and moving a full-scale deck specimen back and forth. This evaluation method has also been used in previous studies as a way to evaluate the fatigue durability of decks reinforced with carbon fiber sheets using epoxy resin adhesive.
[0189] In this test, in order to confirm the reinforcing effect of the reinforcing method according to this embodiment, a wheel load running test was conducted on an ordinary RC deck reinforced using this reinforcing method, with the same specimen dimensions and test conditions as those in previous literature 1.
[0190] The dimensions of the specimens used in this test and the arrangement of the rebars are as shown in Figure 13. The concrete mix is as shown in the table in Figure 14.
[0191] The test specimen was 2000 mm (length perpendicular to the bridge axis) x 3000 mm (length in the bridge axis direction) x 180 mm (thickness), and the deck had a haunch (50 mm) at the end. Fiber-reinforced sheets 40, FSS-MM-450ME (C1) manufactured by Nippon Steel Chemical & Material Co., Ltd., were attached to the deck, 250 mm wide pieces spaced 150 mm apart, one layer at a time vertically and horizontally, using polymer cement mortar 50 (see Figure 12). After curing was completed, a wheel load running test was carried out.
[0192] The loading conditions in this test were the same as in previous studies, and were the staircase loading conditions shown in Figure 15. The horizontal axis is the number of runs, and the vertical axis is the wheel load, with a load of 150kN for the initial 100,000 runs, 180kN thereafter until 800,000 runs, 210kN until 1,000,000 runs, and then increasing the load by 30kN for each of the 1,050,000, 1,150,000, and 1,200,000 runs, and the fatigue durability was evaluated based on the increase in deflection in the center of the deck.
[0193] The test results, as shown in Figure 16, confirmed a reinforcing effect that was comparable to previous research. It was estimated that the concrete floor slab (fireproof floor slab reinforcement) using the reinforcing method according to this embodiment has a lifespan that is 30 times longer than floor slab reinforcement using conventional methods, and it was found to have a sufficient reinforcing effect.
[0194] The present invention is not limited to the above-described embodiment, and various modifications, changes, and improvements are possible without departing from the spirit and scope of the present invention. [Explanation of symbols]
[0195] 10 Reinforcement structure 20 Water-based epoxy primer 22 Primer layer 29 Mixed layer 40 Fiber Reinforced Sheet 42 Reinforced Fiber 43 Fiber-reinforced plastic wire 45 Wire fixing material 47 Matrix Resin 50 Polymer cement mortar 52 Binder layer 90 Structure 90A Reinforced surface
Claims
1. A method for reinforcing a structure, comprising: drawing a plurality of fiber-reinforced plastic strands containing reinforcing fibers in a longitudinal direction in a curtain-like shape; fixing the fiber-reinforced plastic strands to each other with a strand fixing material; and bonding the resulting fiber-reinforced sheet to the surface of the structure with a bonding material; applying an aqueous epoxy primer having an aqueous epoxy resin base and a curing agent to the surface of the structure; applying a polymer cement mortar as the binder to the surface of the structure to which the water-based epoxy primer has been applied; a step of pressing the fiber-reinforced sheet against the applied layer of the polymer cement mortar before the applied polymer cement mortar hardens, thereby embedding the fiber-reinforced sheet and adhering it to the surface of the structure; having The fiber-reinforced sheet has inorganic powder attached to the outer periphery of a plurality of the fiber-reinforced plastic strands, The polymer cement mortar has a flow value of 140 to 180 mm in a JIS flow test, a sagging amount of 10 mm or less in the JHS-416-2004 Section Repair Material Quality Standard Test Method, and a tensile strength of 2.5 N / mm in a uniaxial direct tensile strength test at a material age of 28 days. 2 The tensile stress at the time of reaching a tensile strain of 1.5% in the same test is 35% or more of the tensile strength. Methods for reinforcing structures.
2. The polymer cement mortar contains reinforcing organic fibers in an amount of 0.9 to 1.5 vol %. The method for reinforcing a structure according to claim 1.
3. The reinforcing organic fiber contained in the polymer cement mortar is The fiber length is 6 to 12 mm, The aspect ratio is between 120 and 1200. The method for reinforcing a structure according to claim 1.
4. The polymer cement mortar includes fine aggregate, The maximum diameter of the fine aggregate is 0.2 to 1.2 mm; The coarse grain ratio (F.M.) is 0.5 to 2.
3. The method for reinforcing a structure according to claim 1.
5. In the fiber-reinforced sheet, the distance between the fiber-reinforced plastic strands is more than 3 mm and not more than 10 mm. The method for reinforcing a structure according to claim 1.
6. The inorganic powder attached to the fiber-reinforced sheet is The average particle size is 0.900 mm or less, 400 to 2000 g / m per unit area of the fiber-reinforced sheet 2 Attached The method for reinforcing a structure according to claim 1.
7. The interval between the fiber-reinforced plastic strands is larger than the diameter of the inorganic powder, The ratio of the diameter of the fiber-reinforced plastic strands of the fiber-reinforced sheet, the distance between the fiber-reinforced plastic strands, and the diameter of the inorganic powder is 1:0.5-5:0.03-1. The method for reinforcing a structure according to claim 1.
8. In a reinforcement structure for a structure, a fiber-reinforced sheet is formed by aligning a plurality of fiber-reinforced plastic strands containing reinforcing fibers in a longitudinal direction in a curtain shape, fixing the fiber-reinforced plastic strands to each other with a strand fixing material, and bonding the fiber-reinforced sheet to the surface of the structure with a bonding material, a primer layer disposed on the surface of the structure and formed of an aqueous epoxy primer having an aqueous epoxy resin base and a curing agent; a binder layer disposed on a surface of the primer layer, formed of polymer cement mortar as the binder, and having a mixed layer of the aqueous epoxy primer and the polymer cement mortar at the boundary with the primer layer; A fiber reinforced sheet embedded inside the binder layer; Equipped with The fiber-reinforced sheet has inorganic powder attached to the outer periphery of a plurality of the fiber-reinforced plastic strands, The polymer cement mortar has a flow value of 140 to 180 mm in a JIS flow test, a sagging amount of 10 mm or less in a JHS-416-2004 section repair material quality standard test method, a tensile strength of 2.5 N / mm2 or more in a uniaxial direct tensile strength test at a material age of 28 days, and a tensile stress at a tensile strain of 1.5% in the same test of 35% or more of the tensile strength. Reinforcement structure of the structure.
Citation Information
Patent Citations
Reinforcement of structure
JP1991224901A
Structure reinforcing method
JP2008063758A
Method for reinforcing structure
JP2011208352A